Alumina‐Protected, Durable and Photostable Zinc Sulfide Particles from Scalable Atomic Layer Deposition. (2nd February 2021) - Lange, Thomas; Reichenberger, Sven; Rohe, Markus; Bartsch, Mathias; Kampermann, Laura; Klein, Julian; Strunk, Jennifer; Bacher, Gerd; Schlögl, Robert; Barcikowski, Stephan
Abstract: Zinc sulfide has unique and easily modifiable photophysical properties and is a promising candidate for photocatalysis and optoelectronic devices. However, ZnS suffers from corrosive decomposition during excitation processes like UV irradiation, which drastically limits its field of potential applications. For the first time, complete photostabilization of individual ZnS particles by a dense, durable, and only 3‐nm‐thick Al2 O3 layer, produced by rotary atomic layer deposition (ALD) is reported. In contrast to bare ZnS, the coated particles do not suffer from photocorrosive degradation even under long‐term or high power UV irradiation. The presence of a protection layer covering the entire ZnS surface is additionally confirmed by microscopic and spectroscopic investigations of particle cross‐sections. Further, complete inhibition of the reaction between Ag + ions added as the analyte and the ZnS surface is observed. Durability tests of the as‐prepared Al2 O3 layer upon prolonged exposure to water reveal a significant decrease in the protection capability of the layer, which is ascribed to the hydrolysis of the amorphous Al2 O3 . A calcination step at 1000 °C after the ALD treatment, which leads to crystallization of the amorphous Al2 O3 layer, successfully suppresses this hydrolysis and produces an insulating, dense, and inert protection layer. Abstract : The surface stabilization of ZnS particles by an inert and durable alumina coating, produced by rotary atomic layer deposition is presented. The layer completely suppresses the corrosive degradation of the highly susceptible ZnS, without altering its photophysical properties. The stabilization approach is transferable to the whole class of oxidation‐prone sulfides and can advance their application as optoelectronic or energy materials.